The structure of exports and revealed comparative advantage of the world largest exporters - Fronczek, Małgorzata (Struktura towarowa eksportu a przewaga komparatywna w handlu największych eksporterów światowych, 2018)
The aims of this paper are to estimate the revealed comparative advantage of the largest world exporters – the USA, Germany and China – in the years 2000-2014 and compare the comparative advantage index with the structure of their exports. The classical RCA and the modified RCADVA index (based on value added) were used for estimating revealed comparative advantage in foreign trade. The analysis shows that the USA had comparative advantage in the trade of agricultural products and services. Germany and China had comparative advantage in the trade of manufactured products. It was ascertained that the correlation between the share of a given good or service in total exports of the countries under study and the RCADVA index was positive. The structure of Chinese exports was the most consistent with the comparative advantage index, whereas the structure of US exports was the least consistent with this index.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2018; Nr 523, s. 128-137
Keywords: trade in value added; revealed comparative advantage; RCA; exports; handel według wartości dodanej; przewaga komparatywna w handlu